2019
DOI: 10.1007/s00109-019-01852-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of transcription factor profiles in polycystic kidney disease (PKD): identification and validation of STAT3 and RUNX1 in the injury/repair response and PKD progression

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic renal disease, caused in the majority of the cases by a mutation in either the PKD1 or the PKD2 gene. ADPKD is characterised by a progressive increase in the number and size of cysts, together with fibrosis and distortion of the renal architecture, over the years. This is accompanied by alterations in a complex network of signalling pathways. However, the underlying molecular mechanisms are not well characterised. Previously, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…A study has purported that the expression of RUNX1 is markedly enhanced in renal fibrosis 16 . It has been demonstrated that RUNX1 expression is notably heightened in the nuclei of renal epithelial cells, also in human autosomal dominant polycystic kidney disease samples 25 It is reported that miR-21-5p is highly enriched in EPCs-exosomes 26 . It was reported by our study that exosomes raised miR-21-5p and decreased RUNX1 in renal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A study has purported that the expression of RUNX1 is markedly enhanced in renal fibrosis 16 . It has been demonstrated that RUNX1 expression is notably heightened in the nuclei of renal epithelial cells, also in human autosomal dominant polycystic kidney disease samples 25 It is reported that miR-21-5p is highly enriched in EPCs-exosomes 26 . It was reported by our study that exosomes raised miR-21-5p and decreased RUNX1 in renal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Runx1 regulates EMT in other tissues [44][45][46][47]. While the role of Runx1 during kidney development is unknown, it is activated in kidney during injury and repair where it may contribute to several disease processes [23,[48][49][50][51], including cancer [52,53], in which it may collaborate with Runx2 [54] to drive EMT associated with worse outcomes. The profound consequences of Runx1 loss to the mK4 transcriptome suggests that a further delineation of its role in the kidney may be warranted.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Whether expression of Runx1 alters propensity for arrhythmias warrants future investigation. With regards to non-cardiac diseases, increased RUNX1 expression is a key contributor to retinal vascular dysfunction 44 , liver disease 52 , septic shock 53 and kidney dysfunction 54 . In support of our work on the therapeutic potential of RUNX1 inhibitors in the setting of myocardial infarction, Ro5-3335 has been successfully used to improve both cardiac 55 and non-cardiac related diseases 56 .…”
Section: Discussionmentioning
confidence: 99%